TEACHING CAUSATIVE BY USING INDUCTIVE WAY - Dwi Andriani (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
The main problem of this study is, â€œIs it effective to use inductive way in teaching causative to the eleventh grade students of SMA Muhammadiyah 9 Rawa Bening OKU Timur?â€The method used in this study was pre-experimental method in one group pretest posttest design. The population was the eleventh garade students of SMA Muhammadiyah 9 Rawa Bening OKU Timur. The total number was 115 students, consisting three classes. The writer took one class as sample by using convenience non random sampling. It was XI.IPA.I, the total number was 40 students. It was found that the average score in pre-test was 6.29, the average score in post-test was 7.00.The data was analyzed by using matched t-test formula. The result showed the t-obtained was 4.73. On the other hand, the critical value was 1.684 in df (39). Here, t- obtained was higher than t-table. It means that teaching causative by using inductive way to the eleventh grade students of SMA Muhammadiyah 9 Rawa Bening OKU Timur was effective.